Study of the effect of formulation variables on the characteristics of combination tablets containing enalapril maleate and indapamide as active substances using experimental design - Szabó Zoltán-István; Székely-Szentmiklósi Blanka; Deák Boglárka; Székely-Szentmiklósi István; Kovács Béla; Zöldi Katalin; Sipos Emese (Acta Pharmaceutica)
To evaluate the influence of different variables on tablet formulations containing enalapril maleate and indapamide as active substances, two separate experimental designs were employed: one for evaluating powder properties and the other for tablet characteristics. Because of the low active pharmaceutical ingredient content, it was hypothesized that both powder and tablet properties could be determined only by the characteristics of excipients. In order to test this assumption, both experimental designs were done with placebo mixtures. The optimized formulation was then evaluated both with and without APIs. Results indicated that filler and lubricant percentage, along with compression force, were the most important variables during the formulation study. The optimized formulation showed similar characteristics in both cases for all responses, except for angle of repose and friability where only minor differences were observed. The combination of the applied approaches (using placebo composition and fractional experimental design) proved to be efficient, cost effective and time saving.